(3eLehYI QSGFds - (3eLghds
(3ChdgG (B:s
(3ef EfTGFg aj haGA Gdfjd GdeHGQc Yf Gdedc GdfGUQ UdGM GdOjf fhQ Gddg VQjMg s
(3BNQgG (B:s
(3hEdG aHfh ESQGFjd CbGehG deG ZVH Ydjge CQHYjf SfI de ojhdO dge ehdhO s
(3HChdgG UhQI hba eDQNI SfI (B1239(3g`s
(3hChQGbgG JMJGL Edi JQJjHs
(3heYgG eG gh aj ZjQ af GdCOHs
(3HYVgG ef EfTGA cGJH GdSJQ GdTQja HeUQ GdbGgQI (B" (3aj GdbQf GdKGef GdgLQj(B"s
(3hGdCejQ MSGe GdOjf oWQfWGjs
(3hZjQgeG s
Keywords: (3GdCOHs